GAMBARAN KARIES GIGI PADA KELUARGA BINAAN PUSKESMAS MENGWI I DI BANJAR SILA DIIARMA, KECAMATAN MENGWI KABUPATEN BADUNG - Ni Putu Nadi Susanti; I Made Budi Artawa; I Nyoman Wirata (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
AbstractBackground: Dental caries is a one of dental diseases that mostly find in society. If dental caries does not treats, it will destroy all of teeth component include pulpa. Then, it become infection on the mucosa around it. Family health service at the health centre is a group of poor family, family who have pregnant mom with high of risk, and family who have low income and also not yet use health service, that condition has a high risk of the dental caries. The problem is family didn't know about dental caries. The objective of this research is to know about dental caries on family health service at the of health centre Mengwi I. Methode: This research is a descriptive research with 37 people for its population. The analyze of the data is doing by univariate statistic. Results: of this research show that the frequency of dental caries is 54 teeth with percentage 67,57% for people who caries. The mostly frequency of dental caries happen on family with poor criteria. The highest happen on family with bad nutrition with average of the dental caries 1,46. Toot that often had dental caries is first molar teeth mandibular permanent right bottom. The conclution is the frequeney of the dental caries that mostly happen on family who on poor condition and teeth that often had caries is first molar teeth mandibular permanent right bottom. The suggestion for the dental health staff to more respect about the dental health on family heatth service.